Exploring the Benefits of Using Gamification and Videogames for Physical Exercise: a Review of State of Art - González-González, Carina; Gómez del Río, Nazaret; Navarro-Adelantado, Vicente (International Journal of Interactive Multimedia and Artificial Intelligence (IJIMAI), 2022)
There is a lack of motivation in children and adolescents to do physical exercise and at the same time a worldwide obesity epidemic. Gamification and active videogames can be used to increase the motivation of young people, promoting healthy habits. In this work we explore different studies on active videogames, eSports and gamification applied to physical exercise and health promotion. Main findings include positive effects in a reduction in body weight and in the promotion to continue performing of physical exercise. It also contributes to increase the motivation in children and adolescents to practice exercise. The personalization of user experience and emerging technologies (big data, wearables, smart technologies, etc.) are presented as promising opportunities to keep the engagement in game-based program and gamification of physical exercise.
Keywords: videogame; gamification; physical exercise; literature review; state of the art; IJIMAI